2013
DOI: 10.1016/j.ajpath.2013.04.027
|View full text |Cite
|
Sign up to set email alerts
|

An ENU Mutagenesis-Derived Mouse Model with a Dominant Jak1 Mutation Resembling Phenotypes of Systemic Autoimmune Disease

Abstract: Within the Munich, Germany, N-ethyl-N-nitrosourea mouse mutagenesis program, we isolated a dominant Jak1 mouse model resembling phenotypic characteristics related to autoimmune disease. Chromosomal sequencing revealed a new Jak1 (p.Ser645Pro) point mutation at the conserved serine of the pseudokinase domain, corresponding to a somatic human mutation (p.Ser646Phe) inducing a constitutive activation of the Janus kinase (JAK)/STAT pathway. Morphologically, all Jak1(S645P+/-) mice showed a progressive structural d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 87 publications
(75 reference statements)
3
32
1
Order By: Relevance
“…Nonetheless, WT BM cells transferred into Spade-mutant jci.org Volume 126 Number 6 June 2016 mice should be a useful model to investigate the presymptomatic pathological changes in the skin under emollient treatment, which is difficult to investigate in humans. While the present article was in preparation, Sabrauski et al reported that a missense point mutation (S645P) in the pseudokinase domain of the Jak1 gene resulted in dermatitis accompanied by STAT3 activation (41). However, there are important differences between our results and theirs with respect to disease onset and phenotype.…”
Section: Discussioncontrasting
confidence: 63%
“…Nonetheless, WT BM cells transferred into Spade-mutant jci.org Volume 126 Number 6 June 2016 mice should be a useful model to investigate the presymptomatic pathological changes in the skin under emollient treatment, which is difficult to investigate in humans. While the present article was in preparation, Sabrauski et al reported that a missense point mutation (S645P) in the pseudokinase domain of the Jak1 gene resulted in dermatitis accompanied by STAT3 activation (41). However, there are important differences between our results and theirs with respect to disease onset and phenotype.…”
Section: Discussioncontrasting
confidence: 63%
“…This could explain the earlier failure of the JAK3/SYK blocking agent R333 in a clinical CLE study (45). A central role for JAK1 in CLE-associated immune signaling also is supported by recent findings of mice developing CLE-like skin lesions due to JAK1-hyperactivation (46). Currently, a phase II clinical trial investigates the efficacy of orally administered JAK1 inhibitor filgotinib in female patients with active CLE (NCT03134222).…”
Section: Discussionmentioning
confidence: 91%
“…These targets may include TRP channels, as previous studies have demonstrated, these proteins can be phosphorylated to modulate neuronal activity . Strikingly, recent studies in both mice and humans have identified activating mutations in JAK1 that result in pruritic dermatoses . Bone marrow transplantation with wild‐type bone marrow into mutant JAK1 mice, as well as potent systemic immunosuppression in patients with activated mutant JAK1, did not resolve the aberrant inflammation and chronic itch.…”
Section: Effects Of the Immune System On The Sensory Nervous Systemmentioning
confidence: 99%